Risk Factors Dengue Fever in an Endemic Area in Sikka, Indonesia; A Case-Control Study - Erwin, Avelinus Serbianus Nong; Noor, Nur Nasry; Wahiduddin; Arsin, A. Arsunan; Ishak, Hasanuddin; Junus, Andi Julia (National Journal of Community Medicine, 2024)
Background: Dengue fever is a serious health problem that burdens public health and the economy. The aims to analyzing the risk factors for dengue fever in endemic areas in Sikka Regency. Methodology: This research uses a case control study design with a ratio of 1:1. Cases are families whose members were diagnosed with dengue fever based on positive dengue NS1/IGM laboratory results (132). Controls are families whose members do not suffer from dengue fever coming from the same group as cases (132). Multivariate analysis with logistic regression in the STATA application. Results: The total number of cases was 132 cases, (51%) male, with the majority in the 5–15-year age group (39.3%). House Index (62.5%), Breteau Index (386%), Container Index (49.93%), ABJ (37.5%). Multivariate analysis of variables that were risk factors were knowledge (AOR 2.48; 95% CI, 1.128- 4.928), habit of hanging up used clothes with value (AOR 2.93; 95% CI, 1.292 - 6.688), habit of storing water. in open containers (AOR 2.53; 95% CI, 1, 257- 5.090), residential density (AOR 2.20; 95% CI, 1.153 – 4.229), and the dominant risk factor is larval density (AOR 13.97; 95% CI, 6.793 – 28.735) with a probability (96.8%) of causing dengue fever. Conclusions: Behavioral factors that influence the incidence of dengue fever are knowledge, attitude, the habit of hanging up used clothes, the habit of storing water in open containers, and the habit of not draining water containers regularly, while wearing long-sleeved clothes and the use of medication have no influence on the incidence of dengue fever.